CLIMATE DURING PERMIAN-TRIASSIC BIOSPHERE REORGANIZATIONS, ARTICLE 1: CLIMATE OF THE EARLY PERMIAN - Chumakov N.M.; Zharkov M.A. (My University, 2002)
The Permian was marked by transition from the glacioera to the thermoera, the last one in the geo- logical history. This global climatic reorganization followed the significant paleogeographic changes related to Pangea formation and preceded the major reorganization in the Earth's biota that occurred in the terminal Per- mian-initial Triassic. Climatic changes served as a coupling process in this chain of events. The analysis of cli- matic history makes it possible to estimate the role of climate in the cardinal reorganization of the Late Paleo- zoic biosphere. The compiled one lithological-paleogeographic and two paleoclimatic maps allowed recon- struction of the Early Permian climatic zonation. In the initial Permian, glaciations developed in high and middle latitudes of the Southern Hemisphere and resembled the Pleistocene glacial maximum. Later on, the ice shield gradually decreased and in the late Sakmarian-initial Artinskian, it approached the shape of a polar cap. Separate glaciation centers were preserved only in Antarctica until the end of the Permian. These climatic changes were not unidirectional and showed different-scale oscillations. The Permian climate was strongly influenced by the Pangea supercontinent. The asymmetric position of continental blocks relative to the equator determined by an asymmetry in climatic zoning. It was particularly well manifested at the beginning of the Per- mian, when the glacial belt in the past continental southern hemisphere extended from the pole to 40 ° -30 ° S. Correspondingly, other climatic belts in the southern hemisphere were reduced except for the arid one. To the contrary, the glacial belt was missing in the oceanic northern hemisphere, where most developed were semiarid and temperate belts. By the end of the Early Permian, the asymmetry in position of climatic belts slightly decreased. Arid and semiarid climatic belts were widely developed in both hemispheres. The growing aridity of the Pangea supercontinent was caused by its huge dimension, orographic barriers, and successive regression of epicontinental seas and strengthened by the global postglacial warming.
Keywords: Early Permian; glacial; cool–temperate; temperate; semiarid; arid; and equatorial climatic belts; climatic asymmetry; glaciations; oscillations; Triassic; Permian; Mesozoic::Triassic; Paleozoic::Permian; Мезозой::Триасовая; Палеозой::Пермская